Dog Days: Diary of a wimpy kid - "Kinney, Jeff" (Camberwell; Puffin Books, 2009)
It's the summer holidays, the weather's great, and all the kids are having fun outside. So where's Greg Heffley? Inside his house, playing video games with the shades drawn. Greg, a self-confessed 'indoor person, ' is living out his ultimate summer fantasy: no responsibilities and no rules. But Greg's mom has a different vision for an ideal summer
Keywords: Diary fiction-English fiction